Herpesvirus‐bacteria synergistic interaction in periodontitis. Issue 1 (18th December 2019) - Chen, Casey; Feng, Pinghui; Slots, Jørgen
Abstract: The etiopathogenesis of severe periodontitis includes herpesvirus‐bacteria coinfection. This article evaluates the pathogenicity of herpesviruses (cytomegalovirus and Epstein‐Barr virus) and periodontopathic bacteria ( Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis ) and coinfection of these infectious agents in the initiation and progression of periodontitis. Cytomegalovirus and A. actinomycetemcomitans / P. gingivalis exercise synergistic pathogenicity in the development of localized ("aggressive") juvenile periodontitis. Cytomegalovirus and Epstein‐Barr virus are associated with P. gingivalis in adult types of periodontitis. Periodontal herpesviruses that enter the general circulation may also contribute to disease development in various organ systems. A 2‐way interaction is likely to occur between periodontal herpesviruses and periodontopathic bacteria, with herpesviruses promoting bacterial upgrowth, and bacterial factors reactivating latent herpesviruses. Bacterial‐induced gingivitis may facilitate herpesvirus colonization of the periodontium, and herpesvirus infections may impede the antibacterial host defense and alter periodontal cells to predispose for bacterial adherence and invasion. Herpesvirus‐bacteria synergistic interactions, are likely to comprise an important pathogenic determinant of aggressive periodontitis. However, mechanistic investigations into the molecular and cellular interaction between periodontal herpesviruses and bacteria are still scarce. Herpesvirus‐bacteria coinfection studies may yield significant new discoveries of pathogenic determinants, and drug and vaccine targets to minimize or prevent periodontitis and periodontitis‐related systemic diseases.